2019
DOI: 10.4314/contjas.v6i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Mobilities? Experiencing and Responding to Othering in a Borderless West Africa

Abstract: This paper seeks to interrogate the processes of othering that takes place in Ghana, acountry with a long history of migrants from the region now known as Nigeria. Thepaper draws on Spivak's (1985) concept of othering and explores both the ways inwhich Ghanaians othering of Nigerians is made manifest as well as the ways in whichNigerians respond to these processes of othering. Ultimately, I argue that until bothGhanaians and Nigerians recognize othering as a problem worthy of redress, the fullimport of the ECO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Ironically the breach of the Protocol in the form of shop closures has the potential of undoing the integration that has occurred before the Protocol and those that were occasioned by it. A study by Darkwah has demonstrated increases in anti-immigrant sentiments in Ghana (Darkwah, 2020).…”
Section: Challenges Associated With Implementation Of the Free Moveme...mentioning
confidence: 99%
“…Ironically the breach of the Protocol in the form of shop closures has the potential of undoing the integration that has occurred before the Protocol and those that were occasioned by it. A study by Darkwah has demonstrated increases in anti-immigrant sentiments in Ghana (Darkwah, 2020).…”
Section: Challenges Associated With Implementation Of the Free Moveme...mentioning
confidence: 99%